(3OQGSI GdYed aj GWGQ EOGQI GdGfJGL hGdYedjGJs - (3LdGd eMeO(B, (3GdfYjejs ((3YeGf(B:s (3EKQGA ddfTQ hGdJhRjY(B,s, 2009)
(3GdeONd dOQGSI GdYed(B- (3GdEfJGLjI hOQGSI GdYed(B- (3OQGSI GdMQcI(B- (3bjGS GdYed(B- (3JMOjO YOO GdeTGgOGJ GdeWdhHI(B- (3JbOjQ eYOd GdCOGA(B- (3JMOjO GdhbJ GdbjGSj(B- (3GdYed HGdeYGjfI(B- (3EOGQI bhI GdYed(B- (3GdgfOSI GdHTQjIs
(3GdeQGLY U(B.288s
Keywords: (3EOGQI GdEfJGLs; (3GdYed hGdYeGds; (3HMhK GdYedjGJs; (3Jbjje GdCOGAs